2021
DOI: 10.1097/meg.0000000000002142
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of symptomatic uncomplicated diverticular disease could be lower than expected: a single-center colonoscopy-based cohort study

Abstract: Aim The real prevalence of symptomatic uncomplicated diverticular disease (SUDD) is still unknown. The aim of this study was to assess the prevalence of SUDD, post-diverticulitis SUDD (PD-SUDD) and irritable bowel syndrome (IBS)-like symptoms in a real-life population. Methods A cohort of patients, submitted to colonoscopy from 1st January 2012 to 30th April 2018 was revised. Results A cohort of 5451 patients with diverticulosis was identified during the study period. Abdominal pain was recorded in 1141 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…Only a minority will develop acute diverticulitis (AD), characterized by acute inflammation of the diverticula [ 1 ]. Although the prevalence of SUDD and AD are lower than expected [ 2 , 3 , 4 ], we do not yet know why some patients with diverticulosis develop symptoms while others do not. There are data in the recent literature pointing out the possible role of gut microbiota (GM) as a critical factor in the pathogenesis of several gastrointestinal (GI) and extraintestinal (EI) diseases, improving the understanding of the highly complex interaction between GM and innate and adaptive immunity in regulating inflammation [ 5 ].…”
Section: Introductionmentioning
confidence: 81%
“…Only a minority will develop acute diverticulitis (AD), characterized by acute inflammation of the diverticula [ 1 ]. Although the prevalence of SUDD and AD are lower than expected [ 2 , 3 , 4 ], we do not yet know why some patients with diverticulosis develop symptoms while others do not. There are data in the recent literature pointing out the possible role of gut microbiota (GM) as a critical factor in the pathogenesis of several gastrointestinal (GI) and extraintestinal (EI) diseases, improving the understanding of the highly complex interaction between GM and innate and adaptive immunity in regulating inflammation [ 5 ].…”
Section: Introductionmentioning
confidence: 81%
“…In an Italian case–control study including 5451 patients with colonic diverticula, Tursi et al found a prevalence of SUDD in 6.8% of patients. 23 Interestingly, abdominal pain was recorded in almost 21% of patients, diarrhea in 5.3%, and constipation in 9.8% among patients with colonic diverticulosis. 23 In a second Italian prospective observational multicenter cohort study (the REMAD Registry), Carabotti et al found that 6.3% of the 490 patients with baseline diverticulosis developed SUDD at one-year follow-up.…”
Section: Symptomatic Uncomplicated Diverticular Diseasementioning
confidence: 96%
“… 23 Interestingly, abdominal pain was recorded in almost 21% of patients, diarrhea in 5.3%, and constipation in 9.8% among patients with colonic diverticulosis. 23 In a second Italian prospective observational multicenter cohort study (the REMAD Registry), Carabotti et al found that 6.3% of the 490 patients with baseline diverticulosis developed SUDD at one-year follow-up. 19 Differently, in a cohort of 310 participants during a mean follow-up time of 6.8 years at the University of North Carolina, Peery et al found that only 1% of participants with diverticulosis reported a protracted left lower quadrant abdominal pain associated with SUDD.…”
Section: Symptomatic Uncomplicated Diverticular Diseasementioning
confidence: 96%
See 2 more Smart Citations